SHELF-BASIN TRANSITION: SEDIMENTOLOGY AND PETROLOGY OF THE SERRAVALLIAN OF THE TERTIARY PIEDIMONT BASIN (NORTHERN ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
During Serravallian time, a shallow—water shelf mantled by northward migratine sand waves occupied the eastern part of the Tertiary Piedrnont Basin (Serravalle Sandstone, Gavi area). Towards the west, the shelf graded into a basinal zone through a series of steps probably controlled by synsedimentary faults. The autochthonous sediments of the shelf—basin transition were sandy siltstones, which are interbedded in the stratigraphical column with sands carried from near—shore arcas by tectonically—triggered sediment gravity flows. On the Proxima] "steps traction currents could rework these sands and re—form sand waves, while in deeper water they were buried without further reworking. Finally, at the western edge of the study area (Cassinasco), "high—dcnsity" turbidity currents flowing towards the ENE depositcd the sands of the Cassinasco Fm. onto the deep bottoni of the basmal zone.Riv. IC. Paleont. Strat.90 pp. 545—564Marzo 1985Two distinct petrofacies characterize the Serravalle hybrid arenites (bioclastic lithic arkoses) and the Cassinasco sandstones (litharenites), pointing to different source terranes. The Cassinasco Fm. was fed by the Alpine fold—thrust belt, comprising Carboniferous metasediments, Permlan igneous rocks, Mesozoic sediments and the Ligurid Allochthon. The paragencsis of lithic fragrnents and the heavy mineral assemblage show that the source rocks bave undergone blueschist facies (eoalpine) and greenschist facies (rnesoalpine) polyphase rnetarnurpllism. The Serravalle arenites bave a similar "aphanite" rock fragment population, but detritus frorn granitoid bodies is prominent and the detrital modes are closer to the Tertiary clastic units of the Apennines.